E-Grocery system designed for shopping malls / Benz Aliff Malik - Malik, Benz Aliff (Faculty of Computer and Mathematical Sciences, 2006)
The main objective of this project is to develop an e-grocery system designed specifically for shopping malls so that it will aid customers in reducing waiting time when shopping for groceries. This project is created after personal experiences regarding grocery shopping. Data are collected through questionnaires and will be analyzed and discussed .Among them, awareness of e-commerce among the public will be analyzed. Weaknesses in today's e-grocery system will also be analyzed and discussed as to how to overcome them in the new system. However, due to certain restrictions and constraints, the scope area will only be limited to Klang. The project will only focus on the customer as well as the developer point of view. The problems, constraints and limitations concerning around the completion of this project will also be discussed. Lastly, after conclusions have been made, there will be a few recommendations as what to expect fi-om this project in the fiiture and any window of improvement for it.